Determining the Degree of Increasing Locomotive Diesel Economic Efficiency by Modernization of the Speed Controller - Bogajevskiy, A.; Arhun, Shch.; Dvadnenko, V.; Ponikarovska, S. (EAI Endorsed Transactions on Energy Web, 2020)
The powerful means of improving the economy of locomotives during modernization is introduction of electric speed and power controllers, including the ability to control the moment of the fuel supply start. In the depot of the South Railway (Kharkiv, Ukraine), the electronic controller for the speed and power of the diesel generator and standard hydraulic speed and power controller were compared by operational tests at two sections of the freight mainline locomotive of 2TE116 type. The tests were being carried out under real operating conditions during 1-year period. The results showed reduction in fuel consumption in operation up to 6% on a diesel generator equipped with an electronic controller. The rate of the increased operational fuel economy can be given in technical materials only in relative units. The obtained results can be used in substantiating the application of various technical control and management systems.